Determinan keragaman pangan pada remaja putri di Kota Tasikmalaya - Hidayanti, Lilik; Saraswati, Dian; Fikrinnisa, Rizka (Jurnal Gizi Klinik Indonesia, 2025)
Determinants of dietary diversity among female adolescents in Tasikmalaya CityBackground: Poor diet quality is the root cause of nutritional problems in adolescent girls, and dietary diversity is a determinant of diet quality.Objective: This study aimed to analyze the determinants of dietary diversity among female adolescents, encompassing individual, parental, and family factors.Methods: The research design employed a cross-sectional approach. Seven (30%) public junior high schools in Tasikmalaya City were randomly selected as research locations. Of the 391 female students selected as research subjects using proportional random sampling, 367 successfully participated in the research and completed the data analysis. The food diversity variable was measured using the Individual Dietary Diversity Score (IDDS) instrument, based on the results of two 24-hour non-consecutive recall methods. Determinants were measured using a structured questionnaire. Bivariate analysis employed Spearman's rank and chi-squared tests, while multivariate analysis utilized logistic regression modeling.Results: Most participants had a non-diverse diet (78.8%). Green, leafy vegetables and vitamin A-rich fruits were food groups consumed by fewer than a third of the subjects. The results of statistical tests revealed that variables such as pocket money, screen time duration, maternal education, maternal employment status, and family income were significantly related to the dietary diversity of adolescent girls (p < 0.05).Conclusions: The length of time female adolescents spent in front of screens (screen time) was the most significant variable influencing the dietary diversity of female adolescents. Therefore, it is necessary to promote healthy snacks made from vegetables and fruit that can be consumed while engaging in activities in front of the screen.